Base-Promoted Regioselective Bromination of Imidazo[1,2-α]pyridines with CBr4 as Bromine Source - He, Pei; Liu, Chunbo; Shen, Qinpeng; Xia, Jianjun; Han, Ying; Xiong, Wen; Li, Zhenjie; Tang, Shiyun; Liu, Zhihua; Zhang, Fengmei (Letters in Organic Chemistry, 2023)
A bromination of hydrocarbons with CBr4 as a bromine source, promoted by NaOH, has been developed. The reaction method with high efficiency and regioselectivity for the synthesis of C3-brominated imidazo[1,2-α]pyridines. An effective and simple method of C-X bond construction has been developed, which is a supplement to the halide of imidazo[1,2-α]pyridines.
Keywords: 2-α]pyridines